Deviations of Language Politeness among Teachers and Students in Online English Learning in 9th Grade at SMP N 1 Pandak - Riswanda Himawan (Universitas Veteran Bangun Nusantara, 2021)
Language politeness is an important element in communication, by paying attention to language politeness, someone is considered to have good character so that what is conveyed can be accepted by the interlocutor. The application of language politeness is very necessary in every speaking activity. This study aims to determine describe the forms of language politeness among teachers and students in English learning activities. This research is included in the type of descriptive qualitative research. So that the data obtained in qualitative form and analyzed descriptively. The method used in this research is the padan pragmatic method by Sudaryanto. The data collection technique used in this research is the technique of with dasar or basic technique in the form of sadap and its lanjutan or advanced technique in the form of simak bebas libat cakap then are continued with rekam or recording and catat or note-taking technique. The results of the analysis show that there is an application or use of language politeness in the teaching and learning process in the English class which is represented in the transactional text English subject for 9th grade at SMP N 1 Pandak.